Threshold effect of inflation on economic growth in Nigeria - Sani Bawa; Ismaila S. Abdullahi (CBN Journal of Applied Statistics, 2012)
It is widely believed that price stability promote long-term economic growth, whereas high inflation is inimical to growth. This paper utilized a quarterly time series data for the period 1981 - 2009 to estimate a threshold level of inflation for Nigeria. Using a threshold regression model developed by Khan and Senhadji (2001), the study estimated a threshold inflation level of 13 per cent for Nigeria. Below the threshold level, inflation has a mild effect on economic activities, while above it, the magnitude of the negative effect of inflation on growth was high. The negative and significant relationship between inflation and economic growth for inflation rates both below and above the threshold level is robust with respect to changes in econometric methodology, additional explanatory variables and changes in data frequency. These finding are essential for monetary policy formulation as it provide a guide for the policy makers to choose an optimal target for inflation, which is consistent with long-term sustainable economic growth goals of the country.
Keywords: E31; O40; 330; Inflation; Growth; Threshold